Menguatkan Moral Anak Generasi Alpha melalui Permainan Tradisional - Zuhdiyah, Zuhdiyah; Choirunniswah, Choirunniswah; Choiriyah, Choiriyah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to analyze the form of moral values formed in Aplha Generation children through traditional games that use songs and how these traditional games can be used to strengthen these moral values. This research was conducted in Seberang Ulu and Seberang Ilir Palembang for children of the Alpha generation. This research is a case study, which is part of qualitative research. Data collection methods are interviews and observation. Data sources include Palembang natives, male or female adults at least 30 years old, educated at least junior high school, knowledgeable about local culture, and have good memory speech. The research data include data on the form of the game and data on the moral values contained in the game. Data analysis was carried out with several stages: data collection, data reduction, data presentation, and conclusion. The results showed that the Angket-angket Periuk, Cup Mak Ilang, and Luk-luk Cino Buto games are Palembang traditional games that have nine forms of moral values, namely moral values of justice, responsibility, self-control, courage, honesty, trust, brotherhood, patience, and wisdom. Strengthening moral values in children occurs when children play, play, and play after playing.